Collective Bargaining in the Public Sector : Prince Edward Island - Cowan, G. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
The author reports on Prince Edward Island's attempt to solve some of the key issues of public sector bargaining through Us recent collective bargaining regulations for teachers and the public service.